2013
DOI: 10.1118/1.4820443
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of photon dose calculation under jaw and MLC shielding

Abstract: The two algorithms analyzed showed encouraging results in predicting out-of-field region dose for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…While agreeing with aforementioned retrospective reports, our clinically optimized synchronous JT‐VMAT plan exhibits superior OAR protection for normal lung doses as well as other OAR sparing prospectively compared to no JT‐VMAT for the given complexity of single‐isocenter/two‐lesion lung SBRT setting. By tracking the jaws during SBRT VMAT plan optimization, the magnitude of normal lung dose reductions (the OAR closest to the multiple targets) observed in this study were generally consistent with previous studies, yet relatively higher differences (up to 11%) were observed, perhaps due to the unique complexity of the clinical situations and the distance between the tumors. It is worthwhile to mention that MLC transmission of our 6 MV‐FFF beam was 1.2% and was modeled by the TPS and incorporated in the dose calculation.…”
Section: Discussionsupporting
confidence: 89%
“…While agreeing with aforementioned retrospective reports, our clinically optimized synchronous JT‐VMAT plan exhibits superior OAR protection for normal lung doses as well as other OAR sparing prospectively compared to no JT‐VMAT for the given complexity of single‐isocenter/two‐lesion lung SBRT setting. By tracking the jaws during SBRT VMAT plan optimization, the magnitude of normal lung dose reductions (the OAR closest to the multiple targets) observed in this study were generally consistent with previous studies, yet relatively higher differences (up to 11%) were observed, perhaps due to the unique complexity of the clinical situations and the distance between the tumors. It is worthwhile to mention that MLC transmission of our 6 MV‐FFF beam was 1.2% and was modeled by the TPS and incorporated in the dose calculation.…”
Section: Discussionsupporting
confidence: 89%
“…Also, PD of FFF beams has been studied for the treatment plans generated for the intensity modulated radiation therapy (IMRT), stereotactic body radiotherapy (SBRT), and stereotactic radiosurgery (SRS) 4,8 as well as for square and rectangular open fields. 7,11,19 Similar to the MC studies, these publications have suggested that the PD of unflattened beams is lower than flattened beams of the same nominal energy and that the relative difference in PD increases with energy.…”
Section: Introductionmentioning
confidence: 55%
“…Peripheral doses are also relevant when considering the risk of secondary malignancies or the potential failure of the implanted electronic devices (e.g., pacemakers, defibrillators). 5,12,15,[17][18][19] Numerous studies have investigated the trends in PD for flattened photon beams with varying field sizes, depth, and distances from the field edge, as well as the effects of beam modifiers [e.g., multileaf collimators (MLCs)] and collimator rotation. 12,[14][15][16][20][21][22][23][24] The removal of the flattening filter changes the profile and dosimetric characteristics of photon beams.…”
Section: Introductionmentioning
confidence: 99%
“…Kron et al 26 and Fogliata et al 27 assessed the accuracy of the AXB11 and the AAA under the shielding by the jaw, the MLC or the both with varying static and VMAT fields. In general, good results were obtained for both algorithms, the largest discrepancies being for the smallest fields.…”
Section: The Axb Algorithm and Homogeneous Phantomsmentioning
confidence: 99%